EFL STUDENTS AND TEACHERS' PERSPECTIVES OF ISOLATED AND INTEGRATED APPROACH IN HIGH SCHOOL - Siregar, Lastri Nita; Puspitorini, Dwi (Premise: Journal of English Education and Applied Linguistics, 2024)
This study examines the perceptions of high school EFL students regarding isolated and integrated approaches to grammar teaching in Depok, Indonesia. Using a qualitative descriptive method, the research investigates how students view and evaluate the effectiveness of these approaches in grammar instruction. Data was collected through questionnaires completed by 113 students. The results show a strong preference for the integrated approach, with 98.3% of students favoring grammar instruction during communicative activities. Although there were some inconsistencies in student preferences, students recognized the benefits of integrating grammar with communicative tasks. However, challenges such as students' tendency to forget grammar rules and difficulties in implementation were noted. This study emphasizes the importance of a balanced approach, combining integrated grammar instruction with structured practice to optimize learning outcomes.